Neurodevelopmental delay in normocephalic children with in utero exposure to Zika virus - Adriana Virginia Faiçal; Juliana Cabral de Oliveira; João Vitor Vieira Oliveira; Breno Lima de Almeida; Iluska Andrade Agra; Luiz Carlos Junior Alcantara; Angelina Xavier Acosta; Isadora Cristina de Siqueira (BMJ Publishing Group, 2019)
Neurodevelopment in 29 normocephalic children with in utero exposure to Zika virus (ZIKV) was evaluated by the Bayley Scales of Infant and Toddler Development-Third Edition. Ten (35%) infants presented neurodevelopment delay. Language, cognitive and motor delays were identified in 9 (31%), 4 (14%) and 1 (3%) infants, respectively. Children exposed to ZIKV in utero must undergo careful evaluations for the early detection of any neurodevelopment delays in order to implement prompt intervention.